SPIN90 Modulates Long-Term Depression and Behavioral Flexibility in the Hippocampus - Kim, Dae Hwan; Kang, Minkyung; Kim, Chong-Hyun; Huh, Yun Hyun; Cho, In Ha; Ryu, Hyun-Hee; Chung, Kyung Hwun; Park, Chul-Seung; Rhee, Sangmyung; Lee, Yong-Seok; Song, Woo Keun (Frontiers in Molecular Neuroscience, 2017)
The importance of actin-binding proteins in the regulation of synapse morphology and plasticity has been well established. SPIN90, an Nck-interacting protein highly expressed in synapses, is essential for actin remodeling and dendritic spine morphology. Synaptic targeting of SPIN90 to spine heads or dendritic shafts depends on its phosphorylation state, leading to blockage of cofilin-mediated actin depolymerization and spine shrinkage. However, the physiological role of SPIN90 in long-term plasticity, learning, and memory are largely unknown. In this study, we demonstrate that Spin90-knockout (KO) mice exhibit substantial deficits in synaptic plasticity and behavioral flexibility. We found that loss of SPIN90 disrupted dendritic spine density in CA1 neurons of the hippocampus and significantly impaired long-term depression (LTD), leaving basal synaptic transmission and long-term potentiation (LTP) intact. These impairments were due in part to deficits in AMPA receptor endocytosis and its pre-requisites, GluA1 dephosphorylation and PSD95 phosphorylation, but also by an intrinsic activation of Akt-GSK3β signaling as a result of Spin90-KO. In accordance with these defects, mice lacking SPIN90 were found to carry significant deficits in object-recognition and behavioral flexibility, while learning ability was largely unaffected. Collectively, these findings demonstrate a novel modulatory role for SPIN90 in hippocampal LTD and behavioral flexibility.